2007
DOI: 10.1142/s0218495807000149
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities as Existing and Created: A Study of Entrepreneurs in the Swedish Mobile Internet Industry

Abstract: The notion of opportunities is fast becoming a central theme in the field of entrepreneurship research. As part of this growing interest, the ontological status of opportunities has been scrutinized with researchers tending to view them as either objectively existing or socially created. In the present treatment, this ontological debate is partly avoided in favor of a phenomenological examination of Mobile Internet entrepreneurs, which naturally bridges these distinctions. The empirical findings are used to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
74
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 58 publications
2
74
0
5
Order By: Relevance
“…Nonetheless, three studies warrant attention: (1) Building on radical subjectivism and employing interpretive phenomenological methods grounded in narrative and theme analysis, Berglund (2007) found that Swedish mobile Internet entrepreneurs perceived opportunities as (in part) created via their subjective expectations of an unknowable future and their continual revision of plans in a fast-paced, uncertain, turbulent market. (2) Baker and Nelson's (2005) comparative case study of resource-constrained firms in an economically depressed mining region in the United States uncovered a process by which entrepreneurs subjectively create unique services by recombining available resources for new purposes.…”
Section: A New Nonequilibrium Economic Approach To Entrepreneurshipmentioning
confidence: 99%
“…Nonetheless, three studies warrant attention: (1) Building on radical subjectivism and employing interpretive phenomenological methods grounded in narrative and theme analysis, Berglund (2007) found that Swedish mobile Internet entrepreneurs perceived opportunities as (in part) created via their subjective expectations of an unknowable future and their continual revision of plans in a fast-paced, uncertain, turbulent market. (2) Baker and Nelson's (2005) comparative case study of resource-constrained firms in an economically depressed mining region in the United States uncovered a process by which entrepreneurs subjectively create unique services by recombining available resources for new purposes.…”
Section: A New Nonequilibrium Economic Approach To Entrepreneurshipmentioning
confidence: 99%
“…Berglund 2007;Foss et al 2007;Foss & Ishikawa 2007;Loasby 2007a;Foss et al 2008) to argue that entrepreneurs' divergent imaginations and the novel products that result from them drive far-from-equilibrium market processes to create not market anarchy, as many scholars assume, but market order. We define "market order" as a coordinated pattern of thoughts and actions that characterizes market processes.…”
mentioning
confidence: 99%
“…The discovery view is often linked with the writings of Shane (2000Shane ( , 2001 while the creation view with the articles by Sarasvathy (2001Sarasvathy ( , 2003. Berglund (2007) has presented a comparison between discovery and creation perspective (TABLE 8).…”
Section: Business Opportunity Views and Their Suitability For Smeoriementioning
confidence: 99%
“…For example, the big demographic change -the phenomenon of population aging -will offer many opportunities for SMEs and those should be examined together. The work of Shane and Venkataraman (Shane & Venkataraman 2000;Shane 2001;Venkataraman 1997) which represents the discovery view, is highly regarded in the literature (Berglund 2007;Cooper 2003, 24-25;Down 2010, 53-54;Kontinen 2011, 25-26;Landström 2005, 19-20). Shane and Venkataraman (2000) support the view of Kirzner and argue that opportunities are discovered by individuals.…”
Section: Business Opportunity Views and Their Suitability For Smeoriementioning
confidence: 99%
See 1 more Smart Citation